2012
DOI: 10.2174/1871523011202030253
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Certain Dihydroxy Flavones and the Mechanisms Involved

Abstract: This study was designed to evaluate the anti-inflammatory action of four dihydroxy flavone derivatives; 3,3'- dihydroxy flavone, 5,6-dihydroxy flavone, 3,7-dihydroxy flavone and 6,3'-dihydroxy flavone and to further investigate the multiple cellular mechanisms underlying the anti-inflammatory effect of these compounds. The effect of dihydroxy flavones on acute inflammation was studied in rats employing carrageenan induced hind paw edema method. Further, the role of proinflammatory cytokines like TNF-α and IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Flavonoids are the class of ubiquitously present plant-derived polyphenolic compounds with widely recognized anti-inflammatory [14, 15], antimicrobial [16], anticancer [17], and antiallergic [18] activities. Isoquercitrin (IQ), a flavonoid, is a widely existing quercetin glycoside present in numerous nutritional sources of vegetables and fruits species [19].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are the class of ubiquitously present plant-derived polyphenolic compounds with widely recognized anti-inflammatory [14, 15], antimicrobial [16], anticancer [17], and antiallergic [18] activities. Isoquercitrin (IQ), a flavonoid, is a widely existing quercetin glycoside present in numerous nutritional sources of vegetables and fruits species [19].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on a few monomethoxy flavones (Muthiah et al 1993), monohydroxy flavones (Arivudainambi et al 1996) and dihydroxy flavones (Umamaheswari 2008;Vidyalakshmi et al 2012) further confirmed the anti-inflammatory potential of flavonoids. In a recent study (Kamalakannan et al 2014) a few structurally related dimethoxy flavones were investigated for their pharmacological actions.…”
Section: Introductionmentioning
confidence: 91%
“…Few polyhydroxy flavones like chrysin, apigenin and luteolin dose dependently inhibited the pro-inflammatory cytokines (IL-1b, IL-6 and TNF-a) production and the metabolic activity of LPS stimulated peripheral blood mononuclear cells (Hougee et al 2005). A recent study (Vidyalakshmi et al 2012) reported significant inhibition of pro-inflammatory cytokine IL-1b by certain dihydroxy flavones.…”
Section: Effect Of Dimethoxy Flavones On Il-1bmentioning
confidence: 99%
See 2 more Smart Citations